Variation in growth traits among progenies of Eucalyptus tereticornis Sm. under flood-plain conditions of Punjab - Dhillon, G.P.S.; Singh, Avtar (Indian Journal of Agroforestry, 2020)
Present study was conducted to estimate genetic variation in growth traits of progenies of Eucalyptus tereticornis Sm. through a trial conducted under flood-plain conditions at Ropar (Punjab) following randomized block design with four replications and plot size of five plants. The seeds of selected trees procured from Australia, Tamil Nadu, Orissa, West Bengal, Chhattisgarh, Haryana and Punjab were used for the study. The data on plant height and collar diameter were recorded at age of 3.5 years. The differences among progenies were significant for both growth traits. Three progenies viz. P58, P76 and P132 attained significantly higher diameter than control, whereas, ten progenies P58, P114, P136, P57, P112, P113, P132, P106, P92 and P122 registered significantly higher height than control. The Punjab source attained relatively higher values and the lowest mean values were in case of Raipur source. The values of the heritability for height and collar diameter were 30.53 and 25.75 per cent, respectively. The genetic gain was 18.20 and 16.06 per cent of general mean for height and diameter, respectively.